The true Finns identity politics and populist leadership on the threshold of the party's electoral triumph - Niemi, Mari K. (Javnost (Ljubljana), 2013)
In the Finnish general elections of 2011 the nationalist-populist True Finns Party gained a ground-breaking victory: its parliamentary group of 5 members grew to 39 members. This article examines the party's leader and co-founder Timo Soini's populist leadership in the context of the Nordic consensual multiparty system. The focus is on the direct communication Soini targeted to the party's (possible) supporters in his Internet blog and columns in the party's paper. Applying populist strategies in the circumstances of a Finnish political reality called for balance on several fronts. First, Soini's rhetoric balanced the dynamics of rousing the troops to the frontlines on the one hand, and integrating them to follow a certain set of behavioural norms and rules for party activities on the other. Although the separation of Žus' and Žthem', typical for populist political strategy, was also substantial in Soini's argumentation, the 'other' was mainly not immigrants but various domestic and European elites. In his leadership, Soini balanced between two central questions. How, on the one hand, could the party be unique and gripping enough to attract support from both formerly passive voters and thosewho tended to vote for traditional parties? How, on the other hand, to remain respectable enough to suit the taste of the traditionally somewhat moderate Nordic voter?
Keywords: Finska; mölkky; parlamentarna demokracija; political party; politične stranke; politična desnica; nacionalizem; nationalism; politične komunikacije; politična propaganda; election; volitve